2007
DOI: 10.1021/jf0728146
|View full text |Cite|
|
Sign up to set email alerts
|

Broccoli: A Unique Vegetable That Protects Mammalian Hearts through the Redox Cycling of the Thioredoxin Superfamily

Abstract: Epidemiological evidence indicates several health benefits of the consumption of broccoli, especially related to chemoprevention. Because broccoli contains high amounts of selenium and glucosinolates (particularly glucoraphanin and isothiocyanate sulforaphane), which can produce redox-regulated cardioprotective protein thioredoxin (Trx), it was reasoned that consumption of broccoli could be beneficial to the heart. To test this hypothesis, a group of rats were fed broccoli (slurry made with water) through gava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 46 publications
1
92
0
1
Order By: Relevance
“…broccoli-enriched diet exhibit significant increases in aortic smooth muscle mitochondrial proteins that could influence PTP opening, including thioredoxin, thioredoxin reductase, glutathione reductase, glutathione, and catalase enzyme activities (Mukherjee et al, 2008). Mitochondria isolated from the livers of rats injected intraperitoneally 40 hours earlier with sulforaphane exhibit elevated immunoreactive levels of glutathione peroxidase 1, thioredoxin 2, and mitochondrial malic enzyme (Greco et al, 2011).…”
Section: Protection Against Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…broccoli-enriched diet exhibit significant increases in aortic smooth muscle mitochondrial proteins that could influence PTP opening, including thioredoxin, thioredoxin reductase, glutathione reductase, glutathione, and catalase enzyme activities (Mukherjee et al, 2008). Mitochondria isolated from the livers of rats injected intraperitoneally 40 hours earlier with sulforaphane exhibit elevated immunoreactive levels of glutathione peroxidase 1, thioredoxin 2, and mitochondrial malic enzyme (Greco et al, 2011).…”
Section: Protection Against Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Nrf2 is widely expressed and it has been studied in many different tissues [7,33,34] . In the cardiovascular system, it has been shown that ischemia/ reperfusion (I/R) down-regulates Nrf2 protein expression in rat heart and that aging decreases glutathione synthesis via diminished Nrf2 signaling in rat vascular endothelial and smooth muscle cells, suggesting that Nrf2 may play a critical role in the development of CVD in the aged population [6,35] . He et al [30] have shown a functionally decreased contractility when Nrf2 is genetically deleted from cardiomyocytes due to a marked increase in high-glucose oxidative stress and apoptosis.…”
Section: Signalingmentioning
confidence: 99%
“…Several animal models suggest that when endogenous anti-oxidant systems are overwhelmed, exogenous antioxidant supplementation can be used for preventive and/or therapeutic intervention of oxidative cardiovascular disorders [35,36] . Phenolic acids are a group of compounds that are widely distributed in natural plant foods including fruits, vegetables and whole grains [36] .…”
Section: Role Of Nutrition In Antioxidant Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for this indirect effect of sulforaphane include increased expression of mitochondrial enzymes that reduce NADP + to NADPH [105] and increased expression of the anti-apoptotic mitochondrial protein, Bcl-2. Cardiac Bcl-2 levels are elevated in rats maintained on a high broccoli diet [106]. Moreover, we have shown that mitochondria within Bcl-2 overexpressing neural cell lines are resistant to PTP opening [107].…”
Section: S433mentioning
confidence: 81%